Adsorption of Malachite Green and Alizarin Red S Dyes Using Fe-BTC Metal Organic Framework as Adsorbent - Delpiano, Giulia Rossella (Int J Mol Sci, 2021)
Synthetic organic dyes are widely used in various industrial sectors but are also among the most harmful water pollutants. In the last decade, significant efforts have been made to develop improved materials for the removal of dyes from water, in particular, on nanostructured adsorbent materials. Metal organic frameworks (MOFs) are an attractive class of hybrid nanostructured materials with an extremely wide range of applications including adsorption. In the present work, an iron-based Fe-BTC MOF, prepared according to a rapid, aqueous-based procedure, was used as an adsorbent for the removal of alizarin red S (ARS) and malachite green (MG) dyes from water. The synthesized material was characterized in detail, while the adsorption of the dyes was monitored by UV-Vis spectroscopy. An optimal adsorption pH of 4, likely due to the establishment of favorable interactions between dyes and Fe-BTC, was found. At this pH and at a temperature of 298 K, adsorption equilibrium was reached in less than 30 min following a pseudo-second order kinetics, with k″ of 4.29 × 10(−3) and 3.98 × 10(−2) g∙mg(−1) min(−1) for ARS and MG, respectively. The adsorption isotherm followed the Langmuir model with maximal adsorption capacities of 80 mg∙g(−1) (ARS) and 177 mg∙g(−1) (MG), and K(L) of 9.30·10(3) L∙mg(−1) (ARS) and 51.56·10(3) L∙mg(−1) (MG).